Public Perception Toward Infrastructure Development in Solo City as a Tourism Destination through Digital Communication: A Case Study of Social Media Discourse on the Joglo Underpass Project - Haryo Kusumo Aji; Christian Andhika Pramudia (PT FORMOSA CENDEKIA GLOBAL, 2026)
Infrastructure development has become an essential component in strengthening urban tourism competitiveness and improving public mobility in contemporary cities. This study aims to analyze public perceptions toward the Joglo Underpass development project in Surakarta City through digital communication on social media platforms. The research also identifies the factors influencing public opinion formation regarding urban infrastructure development within the context of sustainable tourism. This study employed a qualitative case study approach involving interviews, online surveys, field observations, and social media content analysis. Data were collected from community members, government stakeholders, and digital interactions discussing the Joglo Underpass project. The findings indicate that public perception toward the project was predominantly positive because the infrastructure significantly reduced traffic congestion, improved accessibility, enhanced economic activity, and strengthened urban mobility. The study further reveals that public perception was influenced by direct experience, information credibility, social interaction, cultural values, and government responsiveness toward public issues. The findings confirm that digital communication plays a crucial role in shaping public opinion, encouraging participatory governance, and strengthening sustainable tourism branding. Consequently, infrastructure development should be understood not only as a technical urban project but also as a symbolic representation of city identity, public participation, and urban transformation.